Digitalisasi Database Kependudukan Desa Lebih Gianyar - Dewi, I Gst A Ayu Wulan Permana; Putra, I Gede Juliana Eka; Paramitha, A.A. Istri Ita (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
In this digital era, many people do not yet know about technological developments, especially the role of information technology. Where the role of technology in developing village websites is very important. There are several problems experienced by more villages where the village community has not been able to develop a website perfectly, for example, such as not having entered information about the advantages of more villages and information about more village population data. Based on the problems experienced by the village, regarding the development of the village website, the village government and also the Gianyar district community and village empowerment service are collaborating with Primakara University through the Merdeka Belajar-Kampus Merdeka (BMKM) program with the Final Project scheme.